Optimasi Jumlah Kedatangan KRL Commuter Line untuk Mengatasi Penumpukan Penumpang Jalur Bekasi - Jakarta Kota Menggunakan Simulasi Promodel - Mirna Lusiani; Steven Chandra (Universitas Bunda Mulia, 2018)
A very large KRL/Commuter Line passenger increases at any time will cause problems to be monitored by P.T KAI with an enormous number of passengers who like to fly passenger accumulation. The total arrival of passengers built upon the system is 48182 passengers, with a time of 240 minutes (05.00-09.00). Based on the data analysis, it can be concluded that the model of Commuter Line Bekasi system to Jakarta Kota is currently stored in the passenger capacity whose KRL capacity itself is not enough with the number of passengers not transported is 7483 passengers. To overcome the current passenger accumulation is to use the scenario that has been made that is using the actual time of 14 minutes and increases the number of trains that should be 20 trains to 22 trains. The simulated scenario model result is 3034 passengers transported. Suggestions for further researchers to cope with a perfect passenger pile.